Implementation of Standardized Clinical Processes for TPMT Testing in a Diverse Multidisciplinary Population: Challenges and Lessons Learned. Issue 2 (19th January 2018) - Weitzel, Kristin W.; Smith, D. Max; Elsey, Amanda R.; Duong, Benjamin Q.; Burkley, Benjamin; Clare‐Salzler, Michael; Gong, Yan; Higgins, Tara A.; Kong, Benjamin; Langaee, Taimour; McDonough, Caitrin W.; Staley, Benjamin J.; et al.
Abstract: Although thiopurine S‐methyltransferase ( TPMT ) genotyping to guide thiopurine dosing is common in the pediatric cancer population, limited data exist on TPMT testing implementation in diverse, multidisciplinary settings. We established TPMT testing (genotype and enzyme) with clinical decision support, provider/patient education, and pharmacist consultations in a tertiary medical center and collected data over 3 years. During this time, 834 patients underwent 873 TPMT tests (147 (17%) genotype, 726 (83%) enzyme). TPMT tests were most commonly ordered for gastroenterology, rheumatology, dermatology, and hematology/oncology patients (661 of 834 patients (79.2%); 580 outpatient vs. 293 inpatient; P < 0.0001). Thirty‐nine patients had both genotype and enzyme tests ( n = 2 discordant results). We observed significant differences between TPMT test use and characteristics in a diverse, multispecialty environment vs. a pediatric cancer setting, which led to unique implementation needs. As pharmacogenetic implementations expand, disseminating lessons learned in diverse, real‐world environments will be important to support routine adoption.